An Empirical Research on Fu-Wang Foods Ltd: Industry, Strategy, Accounting, Ratio, Valuation and Proforma Analysis - Islam, K.M. Anwarul (American Finance & Banking Review, 2017)
In this study an attempt was made to prepare the research on Fu-Wang Foods Ltd. We have also analyzed the strategies, accounting policies and ratios. Historical and Proforma income statements, balance sheet and cash flow statement have been made. We have also determined, loosely speaking, the intrinsic value of stocks of firm. The company is in food processing industry. The position of Fu-Wang is good in this industry. Its long term profitability and sustainability is also secured. The accounting policies and estimates of Fu-Wang as well as the food industry are flexible enough. Management enjoys moderate discretionary powers. Analysis of the various ratios over the five years reveals that many of them are satisfactory and some are not. By doing the valuation of the company with some assumption we found the intrinsic value of the firm is approximately 36 tk. Sensitivity of stock price by changing the discount rate and sales growth rate has also been examined. By projecting the historical accounting figures we have also prepared Proforma income statements, balance sheets and cash flow statements and found that the future of Fu-Wang Foods ltd. is rather satisfactory, given some assumptions.